4E.001 Learnings of farmer behaviour from the Victorian Quad Bike Rebate Scheme. (14th March 2021) - Twin, Jimmy; Barker, Samantha; Day, Lauren; McMillan, Janine; Cotton, Jacquie; Adams, Jessie; Taylor, Frances; Silva, Andrea de
Abstract : Background: Quad bikes are a cause of death and serious injury in Australian rural workplaces, with many incidents associated with rollovers. Since 2016, the Victorian Government has funded a rebate scheme for the farming sector to recover costs associated with fitting of a suitably designed and engineered operator protective device (OPD), or for the purchase of an approved side-by-side vehicle with rollover protection and fitted seat belts. The rebate scheme was integrated with an extensive television, print and social media campaign. Methods: An evaluation of the rebate process was carried out by the Institute for Safety, Compensation and Recovery Research (ISCRR). This included an electronic survey completed by 334 farmers and qualitative interviews (n=51) to gain insights into farmer decision-making behaviour. Results: This evaluation identified key factors in determining farmer decision-making in relation to the rebate scheme and were mapped against a health belief model. Barriers to uptake included the initial financial outlay (in particular with side-by-side vehicles). The financial benefit of the rebate scheme was identified as a primary cue to action and key enabler. Conclusion: This study found that Victorian farmer quad bike users had a strong understanding of the dangers and risks involved in quad bike usage. Farmer perception of how these risks applied to their own setting was a major decision-making factor whether to take part in the rebate scheme. Learning Outcomes: The communication a farmer received was likely to influence their perception of rebate scheme benefits, as was the types of supports given.